2014
DOI: 10.1088/1757-899x/64/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

New approach on the catalytic oxidation of methanol to formaldehyde over MoO3 supported on nano hydroxyapatite catalysts

Abstract: Molybdenum oxide (20 wt. %) supported on nano hydroxyapatite mixed was prepared by impregnation method and calcinated at 400 o , 500 o , 600 o and 700 o C in static air atmosphere. The catalysts were characterized by thermogravimetry (TG), differential thermal analysis (DTA), X-ray diffraction (XRD), Transmission Electron Microscope (TEM) and nitrogen sorption measurements. The gas-phase oxidation of methanol to formaldehyde was carried out in a conventional fixed flow bed reactor. The obtained results clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Synthesis of formaldehyde by oxidative dehydrogenation of methanol over MoO 3 supported on non-stoichiometric HAp as a competitive catalyst with previous applied industrial catalysts has been reported, too [39]. In the work by Matsumura and Moffat [40] it was revealed that on hydroxyapatite of stoichiometric composition (Ca/P = 1.65), methanol decomposes at 600°C, in the absence of oxygen, producing predominantly carbon monoxide.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of formaldehyde by oxidative dehydrogenation of methanol over MoO 3 supported on non-stoichiometric HAp as a competitive catalyst with previous applied industrial catalysts has been reported, too [39]. In the work by Matsumura and Moffat [40] it was revealed that on hydroxyapatite of stoichiometric composition (Ca/P = 1.65), methanol decomposes at 600°C, in the absence of oxygen, producing predominantly carbon monoxide.…”
Section: Resultsmentioning
confidence: 99%
“…Under anaerobic conditions a 5 wt% MoO 3 /CaHAP catalyst has previously been reported to have high selectivity and stability for the dehydrogenation of methanol to formaldehyde, although at very low activity, [52,53] but to the best of our knowledge we report the first investigation with oxygen in the feed, making the catalysts relevant for industrial application in the Formox process. This paper reports part one of the investigation, part two was performed on industrial sized catalyst pellets, investigating the influence of pellet density.…”
Section: Introductionmentioning
confidence: 93%
“…The active sites were concluded to be Mo 6+ , which produced Lewis and Brønsted acid sites of weak and intermediate strength [108]. The active phase of the catalyst was suggested to be calcium molybdate formed under calcination [108,109]. Thrane et al [110] investigated MoO 3 supported on hydroxyapatite and the Sr analogue in a feed of 150 NmL/min, 5 vol.% MeOH, and 10 vol.% O 2 in N 2 .…”
Section: Mo Containing Catalystsmentioning
confidence: 99%